Factors Associated With Severe Maternal Outcomes at a Regional Referral Hospital in South-Western Uganda: A Case-Control Study - Dale, Mugisha; Kajabwangu, Rodgers; Mayengo, Horace; Munyanderu, Baraka; Baluku, Asanairi; Manyang, Anthony; Lapat, Jolly Joe; Ssalongo, Wasswa; Kayondo, Musa; Mayanja, Ronald; Boatin, Adeline A; Ngonzi, Joseph (Int J Women’s Health Care, 2020)
Background: The Sustainable Development Goal target is to reduce the global maternal mortality ratio to less than 70 per 100,000 live births by 2030. Maternal morbidity and mortality in sub-Saharan Africa remains high despite global efforts to reduce it. Severe maternal outcome studies offer a panoramic assessment of obstetric care. Objective: The study aimed at determining the factors associated with severe maternal outcomes among women admitted at the obstetrics and gynecology ward of Mbarara Regional Referral Hospital. Methods: In an unmatched case control (1:2) study conducted between February and May 2018, 162 pregnant women admitted on the obstetrics and gynecology ward of Mbarara Regional Referral Hospital, or who had delivered within the past 42 days were recruited. Near miss cases were defined based on the WHO criteria. Near-miss cases and events, maternal deaths and their causes were retrospectively reviewed. Three categories of risk factors (socio-demographic, obstetric and health system) were examined. P-values <0.05 were considered statistically significant. A multivariable logistic regression model was used to identify factors associated with severe maternal outcomes. All analyses were performed using Stata software (Version 12.0, StataCorp, and College Station, TX). Results: In the four-month period there were 2301 live births, there were 45 near miss cases and 9 maternal deaths resulting in a severe maternal outcome ratio of 23.5/1000 live births, maternal near miss ratio of 19.6/1,000 live births, maternal near-miss mortality ratio of 5 and mortality index of 16.7%. Severe obstetric hemorrhage (33%), ruptured uterus (27.8%), sepsis or severe systemic infection (16.7%) and hypertensive disorders in pregnancy (16.7%) were the direct causes of severe maternal outcomes. About seventy-seven percent (77.8%) of the mothers with severe maternal outcomes were referred in from the peripheral health facilities, with a 4-time risk increased risk of a severe maternal outcome (aOR, 4.00; 95 % CI, 1.84-6.66, p-<0.001). Conclusion: Of the severe maternal outcomes, direct causes were the most prevalent and most of which are preventable. Being referred in was significantly associated with severe maternal outcomes. The maternal near miss indicators indicate need for improved quality.
Keywords: Maternal Mortality; Mbarara University; Severe Maternal Outcomes